Role of Ki67 protein in colorectal cancer - Mulyawan, I Made (International Journal of Research in Medical Sciences, 2019)
Colorectal cancer has become one of the most frequent malignancy and the leading cause of death from cancer globally. Global Burden Cancer in 2013 had placed colorectal cancer in third place morbidity level and forth most lethal cancer globally. Understanding prognostic marker is essential to increase prognosis prediction in patients with colorectal cancer, especially in patient with the later stages. Several studies have reported the prognostic value of Ki67 expression in patient with colorectal cancer. Ki67 protein expression is associated with proliferative activation from intrinsic cell population in malignant tumor cells, where Ki67 can be used as a marker for tumor aggressivity. Expressions from protein Ki67 are associated with proliferative activities from intrinsic cell population in malignant tumor cells, where Ki67 can be used as marker from tumor cell’s aggressivity. Several diagnostic applications for pKi67 has already been explained, where Ki67 is significantly higher in malignancy compared to normal tissue. pKi67 is also increased along with the decrease of tissue differentiation, and it correlates with the presence of metastasis that can not be seen and tumor clinical phase. Prognostic value from Ki67 had been investigated in many studies with their potential as reliable marker in breasts, soft tissue, lungs, prostate, cervix, and central nervous system. Positive expression from Ki67 in colorectal cancer shows a better prognosis in patient who received surgical treatment and adjuvant radiochemotherapy, but not in a patient who received only a surgical treatment.